Evaluating the hydrogeological and treatment performance of retrofitted infiltration basins for urban MAR in Cape Town, South Africa - (:unkn) unknown (My University, 2023)
Stormwater harvesting (SWH) has been proposed as a viable way of augmenting water supply in Cape Town, South Africa. Managed Aquifer Recharge (MAR) in retrofitted detention ponds over the Cape Flats aquifer (CFA) has been proposed as the optimal way to implement SWH (Okedi, 2019), but there is currently little experience in how this can be carried out in the very low income, highly contested areas of the City. An existing detention pond in Mitchells Plain, Cape Town, was thus retrofitted to enhance its infiltration capacity and facilitate, inter alia, urban MAR as a pilot investigation. The work was carried out with the local communities' consent and assistance. The pond's hydrogeological and treatment performance was established using a PCSWM model, field studies and column studies. The study has given important insights into how socio-economic context, community engagement and outreach are essential components in the construction and maintenance of retrofits in Cape Town. The hydrogeological performance of the pond was limited by the high-water table (< 2m below ground level). Nevertheless, it was found that the retrofit increased the MAR in the pond by at least 118% for all scenarios. Furthermore, the laboratory studies inform that even with a 0.5 m vadose zone, the CFA soils can remove >76% of stormwater contaminants such as TP, TN, TOC, and heavy metals. This study thus validates the assertion that retrofitted detention ponds can meaningfully contribute to Cape Town's water demand.
Keywords: African Research